Contrasting Views of Citizens’ Assemblies: Stakeholder Perceptions of Public Deliberation on Climate Change - Sandover, Rebecca (2021)
It has been argued that a ‘new climate politics’ has emerged in recent years, in the wake of global climate change protest movements. One part of the new climate politics entails experimentation with citizen-centric input into policy development, via mechanisms of deliberative democracy such as citizens’ assemblies. Yet relatively little is known about the motivations and aspirations of those commissioning climate assemblies or about general public perceptions of these institutions. Addressing these issues is important for increasing understanding of what these deliberative mechanisms represent in the context of climate change, how legitimate, credible and useful they are perceived to be by those involved, and whether they represent a radical way of doing politics differently or a more incremental change. This article addresses these gaps by presenting findings from mixed method research on prior expectations of the Devon Climate Assembly, proposed following the declaration of a climate emergency in 2019. The research compares and contrasts the views of those commissioning and administering the citizens’ assembly, with those of the wider public. Findings indicate widespread support, yet also considerable risk and uncertainty associated with holding the assembly. Enabling input into policy of a broad array of public voices was seen as necessary for effective climate response, yet there was scepticism about the practical challenges involved in ensuring citizen representation, and about whether politicians, and society more generally, would embrace the ‘hard choices’ required. The assembly was diversely represented as a means to unlock structural change, and as an instrumental tool to achieve behaviour change at scale. The Devon Climate Assembly appears to indicate ‘cautious experimentation’ where democratic innovation is widely embraced yet carefully constrained, offering only a modest example of a ‘new climate politics,’ with minimal challenges to the authority of existing institutions.